Tracing Tangible Aspect Around Dr Radjiman Street Corridor in Surakarta : (From the Perspective of Architecture Students) - Subekti, Bambang; Hidayat, Robi; Wardhani, Mustika Kusumaning (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
Street corridors in a historical area are vital in forming an element of the city's image. Dr Radjiman's corridor in Surakarta is part of a historical area containing residents' daily activities. Physically, humans can visually perceive colour, ornament and material elements as a building's facade on two sides of the corridor. This study aims to trace the visual elements in the corridor, which can be seen from the physical aspect. The method used in the research is mixed-methods based, and the respondent data sample obtained is probability sampling. This research can provide a physical description of what is found around the corridor. This research found that visually, the colour, material and ornamental aspects create a diverse mix and match the dominance of white, fabricated materials and cultural acculturation ornaments such as Dutch, Chinese Peranakan and Javanese heritage ornaments. The results of this research can become scientific findings to support efforts to revitalize street corridors in Surakarta.